2015
DOI: 10.4314/tjpr.v14i7.23
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Anticoagulation Knowledge, Anticoagulation Control, and Demographic Characteristics of Patients Attending an Anticoagulation Clinic in Saudi Arabia: A Cross-Sectional Prospective Evaluation

Abstract: %) had good knowledge of warfarin (scored ≥ 75 %), but only 35 patients (33.3 %) had good anticoagulation control (TTR ≥ 75 %). An association was observed between patients with no formal education and poor warfarin knowledge (p = 0.012). Smoking history was also linked with warfarin knowledge (p = 0.025). INR control results significantly differed by marital status with divorced/widow status displaying poor INR control (p = 0.028). Lastly, no association was found between good knowledge and good INR control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
2
14
0
4
Order By: Relevance
“…This hypothesis was also confirmed by other investigations, demonstrating that the greater the patient’s knowledge about treatment with warfarin, the better was the control of oral anticoagulation, as expressed by higher TTR values [ 11 , 20 ]. We observed that formal education and income showed a weak association with the OAK Test, which is similar to the results of other studies that have not demonstrated significant associations between knowledge and these variables as well [ 8 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis was also confirmed by other investigations, demonstrating that the greater the patient’s knowledge about treatment with warfarin, the better was the control of oral anticoagulation, as expressed by higher TTR values [ 11 , 20 ]. We observed that formal education and income showed a weak association with the OAK Test, which is similar to the results of other studies that have not demonstrated significant associations between knowledge and these variables as well [ 8 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding knowledge, although our patients initially received basic information about warfarin in a face-to-face interview supplemented with written material when the medication was prescribed to them and on their registration at the ACC, the baseline level of warfarin knowledge assessed among the patients in this study using the robust validated test, the AKA, showed a significant knowledge gap before the intervention. This result may not be surprising given the consistent findings of unsatisfactory anticoagulant knowledge reported in previous national survey studies[ 24 34 ] based on different knowledge examination tests (such as the Oral Anticoagulation Knowledge [OAK] test). [ 27 ] This finding highlighted the fact that patients may need continuing education, which supports the purpose for conducting this study; other research studies have also suggested that continuing education for long-term warfarin users, together with its sustained beneficial communication between health-care providers and their patients, are mandatory for successful anticoagulant management.…”
Section: Discussionsupporting
confidence: 74%
“…[ 26 27 ] Additionally, according to the protocols of the ACCs in main medical centers in Riyadh, the capital of KSA, alternative services (such as INR testing, warfarin dose adjustment, and side effects monitoring) are offered to a large population. [ 24 34 , 36 ] Providing additional education via an audiovisual intervention to patients who are receiving warfarin could summarize the educational message, improve efficiency in the clinic, and help busy clinics provide other necessary routine services to a larger number of regular visitors to the ACC without compromising staff time and efforts, unlike time- and effort-intensive traditional teaching methods. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, ACC services were introduced in the healthcare system, mainly in Riyadh, in the early 2000s. Currently, ACCs guided by clinical pharmacists have been established in almost every governmental health center [27][28][29][30][31] . Surprisingly, lack of knowledge on basic aspects of warfarin is very high (50-70 %) [27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ACCs guided by clinical pharmacists have been established in almost every governmental health center [27][28][29][30][31] . Surprisingly, lack of knowledge on basic aspects of warfarin is very high (50-70 %) [27][28][29][30][31] . Patients' non-adherence scores are also high, and their satisfaction is poor [30][31][32] , yet these are consistent with those of other international populations 12,33 .…”
Section: Introductionmentioning
confidence: 99%